Anterior cruciate ligament deficiency versus intactness for outcomes in patients after unicompartmental knee arthroplasty: a systematic review and meta-analysis - Guo, Weiming; Wan, Teng; Tan, Haifeng; Fan, Gang; Gao, Xiaoyu; Liu, Pan; Jiang, Changqing (Frontiers in Bioengineering and Biotechnology, 2022)
Objective: The unicondylar knee arthroplasty (UKA) procedure is primarily indicated for osteoarthritis of the knee. Anterior cruciate ligament (ACL) defects have long been considered a contraindication to UKA. However, recent clinical studies have found that ACL defects do not affect postoperative outcomes in UKA. To elucidate whether ACL defects affect postoperative outcomes in UKA, we performed a systematic review and Meta-analysis of observational cohort studies comparing the effects of ACL defects and intactness on surgical outcomes in UKA. Methods: In this study, we used “Anterior Cruciate Ligament”, “Anterior Cruciate Ligament Injuries” and “Arthroplasty, Replacement, Knee” as the subject terms according to PICOS principles. These subject terms and the corresponding free texts were used to conduct a systematic search in the three major databases PubMed, Embase and Cochrane on December 9, 2021. The main study variables included age, gender, region, definition of ACL defect and diagnosed diseases. The study used a random effect model to pool the effect of 95% CIs. To explore the sources of heterogeneity and to test the stability of the results, a sensitivity analysis was performed. Results: The systematic review found no significant differences in postoperative clinical outcomes in the elderly population when unicondylar replacement was performed in the setting of multiple factors such as injury, defects, longitudinal tear, and synovial bursa injury defined as ACL deficiency. The primary clinical outcomes included postoperative revision, Tegner activity score, and Oxford Knee Score (OKS). After statistical meta-analysis, postoperative outcomes such as postoperative revision (OR, 1.174; 95% CIs, 0.758–1.817) and Tegner activity score (OR, -0.084; 95% CIs, -0.320–0.151) were not statistically different. Conclusion: There was no difference in postoperative revision rates and functional outcomes such as Tegner activity score between the ACL-deficient group compared with the ACL-intact group. For the present results, it is not advisable to consider ACL deficiency as a contraindication of UKA.